2001
DOI: 10.1021/bi0113364
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Acetylation of HMG1 Protein Enhances Its Binding Affinity to Distorted DNA Structures

Abstract: The postsynthetic acetylation of HMG1 protein has been known for more than 20 years, but the effect of this modification on the properties of the protein has not been studied so far. Acetylated HMG1 was isolated from cells grown in the presence of sodium n-butyrate and identified as a monoacetylated protein, modified at lysine 2. Acetylated and parental forms of HMG1 were compared relative to their binding affinity to distorted DNA structures. By using mobility shift assay to determine the dissociation constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 54 publications
1
51
0
Order By: Relevance
“…However, acetylation of a single lysine has been shown to alter binding affinity of proteins; for example, binding of highmobility-group 1 (HMG1) protein to DNA (Ugrinova et al, 2001) and binding of nuclear steroid hormone receptors to the ACTR coactivator (Chen et al, 1999). Analogously, monoacetylation of histone H4 is sufficient to alter recognition by transcriptional machinery (Girardot et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, acetylation of a single lysine has been shown to alter binding affinity of proteins; for example, binding of highmobility-group 1 (HMG1) protein to DNA (Ugrinova et al, 2001) and binding of nuclear steroid hormone receptors to the ACTR coactivator (Chen et al, 1999). Analogously, monoacetylation of histone H4 is sufficient to alter recognition by transcriptional machinery (Girardot et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of HMGB1 in vertebrate cells has not been reported. Another modification profile of HMGB1 is the acetylation of Lys 2 and Lys 11 (28,29), and of only Lys 2 (30) in the N-terminal region of the protein from Guerin ascites tumor cells by sodium butyrate treatment. The binding affinity of acetylated HMGB1 for UVdamaged, cis-platinated, and four-way junction DNA is significantly higher than that of the unmodified protein.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both HMGB1 and HMGB2 were acetylated/deacetylated by the same enzymes as those acting on histone H4, indicating the roles of histone acetyltransferases (HATs) and histone deacetylases (HDACs) in the dynamic acetylation of HMGB proteins [109]. Further studies revealed that the acetylated HMGB1 protein, isolated from cells grown in the presence of sodium n-butyrate, exhibited significantly enhanced ability to recognize UV light-or cisplatin-damaged DNA and four-way junction, and the modification site was Lys-2 [110]. In addition, it was found that HMGB1 and HMGB2 were in-vitro substrates for CBP, but not for PCAF or Tip60, and the full-length HMGB1 and HMGB2 were monoacetylated at Lys-2 [111].…”
Section: Ptms Of Hmgb Proteinsmentioning
confidence: 99%